The Role of Organizational Commitment and Employee Compensation in Increasing Employee Productivity In The Pharmaceutical Industry - Asep Sutarman; Nardi Sunardi (JIMF (Jurnal Ilmiah Manajemen Forkamma), 2022)
The purpose of this study is to investigate the role of salary and organizational commitment in boosting employee productivity. 300 people were used as a study sample. To evaluate study data and test research hypotheses, Structural Equation Modeling using SMART PLS version 8.0 was employed. According to the study's findings, direct remuneration had the greatest impact on enhancing staff productivity. According to the indirect impact study, organizational commitment remains an essential variable since it has a positive but not statistically significant effect on staff productivity. It is envisaged that this research would make a significant contribution to pharmaceutical industry stakeholders in terms of increasing corporate productivity. In addition to salary, further study is planned to investigate the possibilities of additional indicators that might boost employee productivity